Effect of Schistosoma haematobium infection on the cognitive functions of preschool age children and benefits of treatment from an endemic area in Zimbabwe - Arthur Vengesai; Maritha Kasambala; Takafira Mduluza; Tariro Mduluza-Jokonya; Luxwell Jokonya; Herald Midzi; Rutendo Birri Makota; Arnold Mutemeri; Emmanuel Maziti; Bazondlile Dube-Marimbe; Dixon Chibanda; Francisca Mutapi; et al. (BMC [Commercial Publisher], 2023)
Abstract